A bibliometric overview of economic sustainability in tourism - Meneses, Daniela (2024)
Multiple research areas have addressed tourism studies, with a recent emphasis on sustainable tourism and the balance between its three dimensions: economic, social, and environmental. We propose an understanding of the significance of economic sustainability in tourism analysis while conducting an extensive bibliometric analysis and critical evaluation of the current literature. Data for this study were extracted from Scopus, a widely recognised database for scholarly research. Specific search terms, including “economic sustainability,” “tourism,” “sustainable tourism,” “economy,” “economic indicators,” and “tourism policy,” were used to gather relevant publications. A total of 1716 documents were initially retrieved. Inclusion and exclusion criteria were applied to ensure the selection of pertinent literature, resulting in 491 publications being retained for further analysis. These publications originated from 234 different sources and involved 1173 authors. The results of the bibliometric analysis reveal promising future research themes, such as sustainable tourism, tourism policy, economic indicators, tourism sustainability, and entrepreneurship. Moreover, identifying the most influential authors and publications offers valuable guidance for future research endeavours.